Seed Accelerator Meet 1.0: Revisiting the gaps, opportunities, and synergies for seed system institutions and actors in India - Nayak, Swati; Hossain, Sk Mosharaf; Mohapatra, Subhasmita; Nath, Anirban; Singh, Varsa; Tyagi, Neeraj Kumar; Singh, Uma Maheswar; Singh, Vikas Kumar; Srivastava, Ashish; Yahaya, Rabe; Habib, Muhammad Ashraful (International Rice Research Institute, 2025)
The Seed Accelerator Meet 1.0, organized by the International Rice Research Institute (IRRI) in collaboration with the National Seed Research and Training Centre (NSRTC), was convened in April 2024 to address critical gaps in India’s rice seed systems. The workshop focused on challenges such as low varietal replacement rates, limited seed access, and weak alignment between breeding, seed delivery, and market demand. Central to the discussions was IRRI’s One Rice Breeding Strategy, which promotes demand-driven, market segment–based product development supported by rigorous multi-location on-farm trials. Evidence from trials conducted across multiple Indian states demonstrated consistent yield advantages of newer varieties over benchmark and farmer-preferred cultivars, highlighting opportunities to accelerate varietal turnover. Through thematic breakout sessions, participants identified institutional, policy, and market-related bottlenecks while proposing strategies involving stronger public–private–community partnerships, digital seed management tools, early-generation seed linkages, and enhanced roles for farmers, millers, and seed enterprises. Overall, the workshop provided a collaborative platform and strategic direction for strengthening rice seed systems, improving varietal adoption, and advancing sustainable and resilient rice production in India.